Pediatric central auditory processing disorder showing elevated threshold on pure tone audiogram. Issue 5 (October 2016) - Maeda, Yukihide; Nakagawa, Atsuko; Nagayasu, Rie; Sugaya, Akiko; Omichi, Ryotaro; Kariya, Shin; Fukushima, Kunihiro; Nishizaki, Kazunori
Abstract: Central auditory processing disorder (CAPD) is a condition in which dysfunction in the central auditory system causes difficulty in listening to conversations, particularly under noisy conditions, despite normal peripheral auditory function. Central auditory testing is generally performed in patients with normal hearing on the pure tone audiogram (PTA). This report shows that diagnosis of CAPD is possible even in the presence of an elevated threshold on the PTA, provided that the normal function of the peripheral auditory pathway was verified by distortion product otoacoustic emission (DPOAE), auditory brainstem response (ABR), and auditory steady state response (ASSR). Three pediatric cases (9- and 10-year-old girls and an 8-year-old boy) of CAPD with elevated thresholds on PTAs are presented. The chief complaint was difficulty in listening to conversations. PTA showed elevated thresholds, but the responses and thresholds for DPOAE, ABR, and ASSR were normal, showing that peripheral auditory function was normal. Significant findings of central auditory testing such as dichotic speech tests, time compression of speech signals, and binaural interaction tests confirmed the diagnosis of CAPD. These threshold shifts in PTA may provide a new concept of a clinical symptom due to central auditory dysfunction in CAPD.